"Rechtsstaat" and "Rule of law" Categories in the Studies of Russian Government Scientists of the early 20th Century - Apolsky, Evgeny A.; Mamychev, Alexey Yu.; Mordovtsev, Andrey Yu.; Zhiltsov, Sergey V.; Magomedov, Rashid M. (Journal of History Culture and Art Research, 2018)
This study examines the theories of Russian pre-revolutionary state scientists on the rule of law, which have been reflected in monographs, dissertations, publications in the periodical legal scientific press of the beginning of the 20th century. The subject of the study is the patterns of evolvement, the content features and results of research undertaken by scientists in the theoretical development of various aspects of a rule of law. The chronological framework is covered by the period from the beginning of the 20th century to 1917, because in the preceding stages the rule of law theory was not developed by Russian government scientists on a serious scientific basis. The conclusion on the qualitative side of the results obtained in prerevolutionary studies that formed the theoretical basis for understanding the essence of the rule of law in the science of Russian state law of this period was formulated in the paper.